Male smoking reduction behaviour in response to China's 2015 cigarette tax increase. Issue 4 (30th May 2019) - Yu, Lingwei; Cohen, Joanna E; Hoe, Connie; Yang, Tingzhong; Wu, Dan
Abstract : Objective: This study aims to evaluate Chinese male smokers' responses to China's 2015 6% ad valorem and RMB0.1 specific excise tax increase per cigarettes pack. Methods: A male population-based cross-sectional survey with multistaged stratified sampling was employed to collect data in six cities in China. Descriptive methods and logistic models were used to assess responses and associated factors following the cigarette tax increase among male Chinese smokers. Results: Among a potential sample of 6500 Chinese males, 6010 individuals were contacted and 5782 participants completed the questionnaires. Of the 2852 current smokers, 60.7% (95% CI: 58.9 to 62.5) did not think cigarettes were expensive, 77.9% (95% CI: 76.4 to 79.5) reported no reduction in smoking in response to the 2015 tax increase and 21.3% (95% CI: 19.8 to 22.8) were not aware of the cigarette tax increase. Smokers who were occasional smokers, intended to quit and thought cigarettes expensive were more likely to report reducing cigarette smoking following the tax increase, while those who had higher household income per capita, smoked more cigarettes, and purchased more expensive cigarettes were less likely to report reducing cigarette consumption. Conclusions: About one in five male Chinese smokers reported reduction in smoking following China's 2015 cigarette tax increase. This is a relatively large impact given the very modest tax increase. Even with the 2015 increase, the excise tax represents only 36.3% of the cigarette price in China. Tax increases are needed to achieve the WHO's recommended level of 70%.